Predictability of meso‐γ‐scale, localized, extreme heavy rainfall during the warm season in Japan using high‐resolution precipitation nowcasts. (10th April 2017) - Kato, Ryohei; Shimizu, Shingo; Shimose, Ken‐ichi; Maesaka, Takeshi; Iwanami, Koyuru; Nakagaki, Hisashi
Abstract : The development and verification of a forecast method for localized, meso‐γ‐scale (2–20 km), extreme heavy rainfall (MγExHR) is important, because it can cause urban flash flooding and inundation with accompanying damage and potential loss of life. Although previous studies have examined the predictability of precipitation at a very short range (≤1 h) using extrapolation‐based nowcasts, they did not specifically focus on MγExHR. In this study, we examine the predictability of 23 selected events of MγExHR (1 h rainfall accumulation ≥50 mm) that occurred during the warm season of 2014 in Japan using High‐Resolution Precipitation Nowcasts (HRPNs) provided by the Japan Meteorological Agency, which are extrapolation‐based nowcasts. Traditional grid‐scale verification using the equitable threat score shows that the HRPNs usefully predict the heavy rainfall areas of ≥20 mm h −1 for at least 12 min at the grid scale of 1 km. Neighbourhood verification using fractions skill scores shows that HRPNs usefully predict the areas of ≥20 mm h −1 up to 29 min by tolerating 11 km displacement errors. After 30 min, a useful forecast cannot be obtained, even if the 11 km displacement errors are tolerated for the ≥20 mm h −1 areas. This result suggests that a numerical weather prediction (NWP) model, whose accuracy is useful after ∼30 min, is necessary to seamlessly provide useful forecasts for heavy rainfall areas of ≥20 mm h −1 for MγExHR with ∼10 km displacement errors, by blending the extrapolation‐based nowcast with NWP.